1993
DOI: 10.1099/00221287-139-7-1487
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and nucleotide sequence of the Butyrivibrio fibrisolvens gene encoding a type III glutamine synthetase

Abstract: A Butyrivibrio fibrisolvens glnA gene encoding glutamine synthetase (GS) was cloned on a recombinant plasmid pGS4 which enabled Escherichia coligfnA deletion mutants to utilize (NH4),S04 as a sole source of nitrogen. The nucleotide sequence of a 2423 bp DNA segment containing the GS-coding region of B.fibrisolvens was determined and the complete amino acid sequence (701 residues) was deduced. Comparisons of the derived B.fibrisolvens GS protein sequence with the amino acid sequences of GS from other bacteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…strain PCC 6803 which contained, integrated into the chromosome, the Anabaena sp. strain PCC 7120 glnA gene (28 (19,43). In fact, it is now possible to define a third family of GSs in bacteria (GSIII) which is not restricted to a single taxonomic group.…”
Section: Insertionalmentioning
confidence: 99%
See 2 more Smart Citations
“…strain PCC 6803 which contained, integrated into the chromosome, the Anabaena sp. strain PCC 7120 glnA gene (28 (19,43). In fact, it is now possible to define a third family of GSs in bacteria (GSIII) which is not restricted to a single taxonomic group.…”
Section: Insertionalmentioning
confidence: 99%
“…Recently, a third GS homologous to prokaryotic GSI has been reported in Rhizobium spp. (9,10,14,40).Besides that, Bacteroides fragilis and Butyrivibrio fibrisolvens, two members of the family Bacteroidaceae which are obligate anaerobic bacteria that live in mammal intestines, contain a GS that differs markedly from all of the GSs previously described in subunit size (Mr, 75,000), structure (hexameric), and amino acid sequence (19,20,43).It has been recently shown that a ginA mutant of the cyanobacterium Agmenellum quadruplicatum was able to grow in the absence of glutamine, indicating that the ginA gene is nonessential for ammonium assimilation and suggesting that another enzyme is responsible for the glutamine synthesis (45).Here we describe the molecular cloning, sequence, and expression of a novel GS gene (glnN) (36). Alternatively, cultures were bubbled with 1.5% (voIvol) CO2 in air.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primers glnA-1 (59-AGGAATATTTTTTGGTTGACA-39) and glnA-2 (59-AACGATTTCCTGTGAATGC-39), amplifying part of the glutamine synthetase encoding gene, on the alignment of the glnA sequence of B. fragilis [17] and Butyrivibrio ®brisolvens were designed [20]. These primers ampli®ed a 780-bp fragment of the glnA gene in a PCR of 35 cycles, with the following thermal pro®le: 948C for 60 s, 528C for 60 s, 728C for 60 s.…”
Section: Dna Extraction and Pcrmentioning
confidence: 99%
“…75,000) than those of GSI or GSII (2, 40, 44). GSIII have been identified in Butyrivibrio fibrisolvens, Ruminococcus albus 8, and some cyanobacteria (2,11,22,35). Five conserved regions have been identified from GSI, GSII, and GSIII proteins.…”
mentioning
confidence: 99%